Business Perspective in Integrating Agricultural Commodity Exchange and Warehouse Receipt System: A decade of Indonesia Experience - Sunarto, Hari; Marwati, Marwati; Hananto, Hans; Yuliawati, Yuliawati (Social Economics and Ecology International Journal, 2018)
This exploratory research on the integration process of Agricultural Commodity Exchange (ACE) and Warehouse Receipt System (WRS) which has been launched since 2008 in Indonesia is based on a business perspective. The study is part of a comprehensive research that has been started in 2008 and is expected to continue until 2019. Data are obtained through  observation, interviews with key informants implementing government  policies, several WRS warehouse managers and ACE, secondary data and surveys to farmers. ACE is meant to increase famers bargaining power and WRS is to increase the price of agricultural commodities as well as part of the national logistics system that supports national food security policies. The efforts of CoFTRA to develop and integrate between ACE and WRS were never stopped since they were introduced in 2008, in fact until now they have not been well integrated. From a business perspective, so far there has not been a choice of sustainable business models for ACE and WRS as business start-ups that benefit all stakeholders, assuming without the support of government subsidies.